2018
DOI: 10.18844/cjes.v13i3.3199
|View full text |Cite
|
Sign up to set email alerts
|

Active learning: let’s make them a song

Abstract: Active learning strategy has an important role in helping students gain 21st century skills such as creativity, collaboration, responsibility and effective communication. By being more active and free in classrooms, students take their own learning responsibility. In this study, we wanted to see the active learning strategy through students’ eyes. Thus, we asked for their views after the completion of the activity. Consequently, students stated they had a lot of fun, felt happy and proud. They also indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Other studies also reported that one of the impacts of songs in English learning was in term of vocabulary retention. Through songs, students can remember and memorize words used in the songs (Shakerian, Rezaei, Murnani, & Moeinmanesh, 2016;Demirci, & Yavaslar, 2018) , even knowing the meaning of new words they acquired without looking up dictionary or asking other people (Shakerian, et.al, 2016).One possible reason on the long-term memory to possibly occur when learners incorporate songs in their learning is since songs are repetitive in nature (Javadi-Safa, 2018).…”
Section: Vocabulary Retentionmentioning
confidence: 99%
“…Other studies also reported that one of the impacts of songs in English learning was in term of vocabulary retention. Through songs, students can remember and memorize words used in the songs (Shakerian, Rezaei, Murnani, & Moeinmanesh, 2016;Demirci, & Yavaslar, 2018) , even knowing the meaning of new words they acquired without looking up dictionary or asking other people (Shakerian, et.al, 2016).One possible reason on the long-term memory to possibly occur when learners incorporate songs in their learning is since songs are repetitive in nature (Javadi-Safa, 2018).…”
Section: Vocabulary Retentionmentioning
confidence: 99%
“…These results were also obtained from research conducted by (Al-sohbani, 2016) who found that conventional learning strategies had no significant effect on students' English skills. Learning English requires an active approach so that students are involved in the learning process (Demirci, 2017;Demirci & Yavaslar, 2018;Rahayu, 2018). Active learning will give students the opportunity to use English so that they will acquire language knowledge automatically.…”
Section: Resultsmentioning
confidence: 99%
“…Such performance will only give people a noisy feeling without any aesthetic feeling of music. The third aspect is that, in terms of timbre, compared with single piano, two pianos have a richer sense of hierarchy and a fuller symphonic quality [ 7 ]. Nevertheless, the timbre of the two pianos should be carried out according to the changes of melody, harmony, voice parts, and tonality, and different timbre should be used to play different voice parts, so as to find the best performance effect.…”
Section: Related Workmentioning
confidence: 99%